(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Data about the new for the southern Ukraine pathogenic fungus Rhizina undulataFr. are provided. The fungus caused illness and following total death of pine-trees seedlings, which were planted in a fall-winter period 2007-2008 in order to replace artificial pine forest (Pinus sylvestris L. , P. pallasianaD. Don.) that had burned out during forest conflagrations in August 2007.